Properties of bacterial rice husk ash concrete. (15th September 2016) - Siddique, Rafat; Singh, Karambir; Kunal,; Singh, Malkit; Corinaldesi, Valeria; Rajor, Anita
Highlights: Calcite producing bacteria improved strength of RHA concrete. Water absorption, porosity and chloride permeability reduced with RHA and bacteria. Abrasion loss was minimum in RHA-bacterial concrete. SEM and XRD analysis indicated the formation of calcite in bacterial concrete. Abstract: Influence of bacteria on the properties of concrete made with rice husk ash (RHA) is presented in this paper. For this purpose, control concrete was designed to have 28-d strength of 32.8 MPa. In the control concrete, cement was partially replaced with (0%, 5%, 10%, 15% and 20% by weight) RHA. Then, bacterium Bacillus aerius (10 5 cells/mL) was mixed in water during making of concrete. Tests were performed for compressive strength, water absorption, porosity, chloride permeability and abrasion resistance up the age of 56 d for all concrete mixtures with and without bacteria. Results indicated that inclusion of bacteria in RHA-concrete enhanced its compressive strength at all ages. However, best performance was achieved with 10% RHA wherein 28-d compressive strength was 36.1 MPa, and with bacteria, it was 40.0 MPa. Inclusion of bacterium in RHA concrete reduced its water absorption, porosity, and permeability at all ages, due to calcite precipitation, which in turn improves these properties. SEM and XRD analysis exhibited the formation of ettringite in pores, calcium silicate hydrate (CSH) and calcite which made the concrete denser. Findings of this investigation indicated the use of RHA and bacterium enhances the durability properties of concrete.